Method for preparing two-dimensional material by stripping bentonite
In the process of preparing two-dimensional materials by bentonite exfoliation, a combined processing method of adding water for pre-exfoliation, adding H2O2 aqueous solution and freezing, and microwave heating and thawing is used to solve the problems of low bentonite exfoliation efficiency and low diameter-to-thickness ratio in the existing technology. Efficient exfoliation and preparation of high-performance two-dimensional materials were achieved.
Patent Information
- Application Number
- CN202411632143.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-21
AI Technical Summary
In the prior art, when preparing two-dimensional materials with bentonite peeling, it is difficult to achieve a high proportion of two-dimensional bentonite with high interlayer peeling efficiency and high diameter and thickness ratio.
Using a combined treatment method of adding water for pre-stripping, adding H2O2 aqueous solution and freezing, and microwave heating and thawing, through high-speed shearing, impurity removal, drying and other steps, the efficient exfoliation of bentonite and the preparation of two-dimensional materials are achieved.
The interlayer peeling efficiency is improved, the proportion of two-dimensional bentonite with high diameter-to-thickness ratio is increased, and the purity and performance of the two-dimensional material are improved.
Smart Images

Figure CN119330366A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for stripping a layered material, and in particular to a method for preparing a two-dimensional material by stripping bentonite. Background Art
[0002] Bentonite is a layered aluminosilicate mineral, and its main component, montmorillonite, has a layered structure. After the layered structure is separated into two-dimensional sheets, the specific surface area of bentonite is increased and the surface activity will be significantly enhanced. The prior art has proposed a variety of methods for exfoliating bentonite to prepare two-dimensional materials.
[0003] Chinese patent document CN112174160A discloses a method for preparing two-dimensional materials by boiling and vaporizing high-purity bentonite at room temperature, wherein the montmorillonite content in the high-purity bentonite is greater than 80%. The main steps include: (1) dispersing bentonite in a lithium chloride or sodium chloride salt solution for ion exchange modification, so that ions with less interaction with the bentonite layers are introduced into the bentonite interlayers to obtain lithium-based / sodium-based bentonite; (2) placing the modified lithium-based / sodium-based bentonite in a basket, and completely immersing the basket in a liquid that can be boiled and vaporized at room temperature, so that the vaporizable liquid first enters the bentonite interlayers through adsorption; (3) removing the basket from the liquid that can be boiled and vaporized, so that the residual liquid in the obtained bentonite is completely vaporized, and the interlayer structure of the bentonite is peeled off by boiling and vaporization.
[0004] Chinese patent document CN117049557A discloses a method for preparing two-dimensional montmorillonite nanosheets with a high diameter-to-thickness ratio. The method comprises the following steps: firstly dispersing montmorillonite in a lithium salt or sodium salt solution for ion exchange modification to obtain lithium-based / sodium-based montmorillonite; then placing the lithium-based / sodium-based montmorillonite suspension in a dialysis bag, and completely immersing the dialysis bag in a dialysis container filled with dialysis fluid; salt ions are transferred to the dialysis fluid through the dialysis bag under the action of concentration difference; when the salt ion concentration in the montmorillonite suspension is lower than the cation concentration between montmorillonite layers, water molecules will enter the interlayers of montmorillonite under the action of osmotic pressure, resulting in osmotic hydration expansion; the montmorillonite hydration expansion action causes the montmorillonite flakes to spontaneously hydrate and peel off.
[0005] Chinese patent document CN 116675254A discloses a method for preparing large-scale high-quality two-dimensional nanosheets by low-frequency microwave thermal method, which adopts low-frequency microwave-assisted method to perform intercalation and exfoliation of inorganic layered materials. Specifically, the inorganic layered material is mixed with an intercalation agent, heated and stirred, and low-frequency microwave treatment is added during the heating and stirring process of the intercalation agent to make the intercalation agent quickly and evenly dispersed in the inorganic layered material, and then ultrasonic vibration is used to exfoliate the intercalation agent.
[0006] Chinese patent document CN117049557A also points out that the commonly used stripping methods for montmorillonite are ball milling and ultrasonic stripping. Ball milling and ultrasonic stripping destroy the interlayer bonding force of montmorillonite through strong physical external forces, so that the montmorillonite lamellae are stripped. These methods, while obtaining montmorillonite nanosheets, destroy the lamellar structure of montmorillonite due to strong physical external forces, and it is difficult to prepare montmorillonite nanosheets with high diameter-to-thickness ratio. In a two-dimensional material and a preparation method thereof proposed in Chinese patent document CN113247868A, a raw material mixture including a viscosity-improving medium and a solvent is first used to prepare a modified fluid, and then the layered raw material powder and the modified fluid are evenly mixed to obtain a mixed paste, and then the mixed paste is subjected to high-speed shear treatment, and then solid-liquid separation is performed. During the high-speed shear process, the mixed paste environment can buffer the mechanical force of high-speed rotation, prevent the lamellar material from being crushed by mechanical impact force, and is conducive to the preparation of large-size two-dimensional materials. Summary of the invention
[0007] The purpose of the present invention is to provide a method for preparing two-dimensional materials by bentonite exfoliation, which is different from the above-mentioned prior art and has a higher interlayer exfoliation efficiency and a higher proportion of two-dimensional bentonite with a high aspect ratio.
[0008] In order to achieve the above object, the technical solution of the present invention is as follows:
[0009] The method for preparing two-dimensional materials by exfoliation of bentonite comprises the following steps:
[0010] S1. Pre-stripping: Put bentonite into water, control the water temperature at 50-80°C, and perform high-speed shearing to pre-strip the bentonite sheet structure. The shearing speed is 3000-8000rpm and the duration is 10-20min.
[0011] S2, impurity removal: the water body after shearing is still, and the impurities precipitated at the bottom are removed after stratification to obtain a stripping dispersion solution;
[0012] S3, drying: drying the exfoliated dispersion solution until the surface of the bentonite is dry;
[0013] S4. Add H2O2 aqueous solution and freeze: Pour H2O2 aqueous solution to cover the surface of bentonite, stir for not less than 30 minutes, and then place in a freezer at a freezing temperature of -18-0°C for not less than 60 minutes;
[0014] S5, microwave heating: thawing the frozen bentonite by microwave heating, accompanied by thermal decomposition of H2O2, so that the interlayer structure of the bentonite is peeled off from each other, and a peeled bentonite dispersion slurry is obtained;
[0015] S6. Drying to obtain the finished product: drying the obtained bentonite dispersion slurry to obtain the finished product.
[0016] Preferably, in step S1, the material-liquid ratio of bentonite to water is 1:5-10.
[0017] Preferably, in step S3, the drying temperature is 250-400° C., and the drying time is 2-5 hours.
[0018] Preferably, in step S4, the mass concentration of H2O2 in the H2O2 aqueous solution is 5-10%.
[0019] Preferably, in step S4, the freezing time is 1-12 hours.
[0020] Preferably, before step S6, steps S4-S5 are repeated 1-2 times.
[0021] The beneficial effect of the present application is that through the coordination of various treatment processes, a set of process flow for preparing two-dimensional materials by using bentonite stripping, which is different from the prior art, is established. After a combined treatment of adding water for pre-stripping, adding H2O2 aqueous solution and freezing, and thawing by microwave heating, the interlayer stripping efficiency is greatly improved, and the proportion of two-dimensional bentonite with a high diameter-to-thickness ratio is relatively high. Among them, another important function of adding water for pre-stripping is to improve the purity of the two-dimensional material. The higher the purity of the two-dimensional material, the better the performance. Secondly, during the freezing and heating process, the extrusion and impact of impurities on the two-dimensional material can be reduced, the probability of two-dimensional material rupture can be reduced, and it is also beneficial to improve the diameter-to-thickness ratio. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 is the SEM image of the original bentonite;
[0023] Figure 2 This is the state diagram of bentonite after pre-stripping and resting;
[0024] Figure 3 This is the SEM image of bentonite after pre-stripping;
[0025] Figure 4 is the AFM image of bentonite particles after pre-stripping;
[0026] Figure 5 AFM image of the finished bentonite nanosheet;
[0027] Figure 6 The diameter, thickness, and diameter-to-thickness ratio size distribution diagram of the finished bentonite nanosheets;
[0028] Figure 7 is the XRD pattern of the original bentonite;
[0029] Figure 8 is the XRD pattern of bentonite after pre-stripping;
[0030] Fig. 9This is a size distribution diagram of the diameter, thickness, and diameter-to-thickness ratio of the finished bentonite nanosheets in Comparative Example 1;
[0031] Fig.10 The XRD diagram of the finished bentonite in Comparative Example 1;
[0032] Fig.11 This is the size distribution diagram of the diameter, thickness, and diameter-to-thickness ratio of the finished bentonite nanosheets that have not been frozen. DETAILED DESCRIPTION
[0033] Example 1
[0034] The bentonite used in the experiment was taken from Xinyang, Henan. The original soil was white, with fine and smooth particles, and passed through a 200-mesh sieve. Figure 1 The following are SEM images of the bentonite, where Figure a is a low-magnification SEM image, showing that the montmorillonite is in the form of particles with a diameter of about 10 μm. Figure b is an enlarged photo of a single montmorillonite particle, where a lamellar structure can be clearly seen.
[0035] The specific stripping steps are as follows:
[0036] S1. Pre-stripping
[0037] Take a 500ml beaker, pour 400ml of clean water, weigh 40g of bentonite, pour it into the beaker, and heat it on a constant temperature heating table, with the temperature controlled at about 70°C. Use a high-speed shearing machine to shear the bentonite in the beaker at a shearing speed of 6000rpm for 15min to pre-strip the bentonite layer structure.
[0038] S2. Impurity Removal
[0039] After 60 minutes of static, the beaker is a uniform dispersion solution with a small amount of precipitation at the bottom. Use a pipette to absorb 80% of the upper dispersion solution to obtain a peeling dispersion solution such as Figure 2 As shown, for comparison, Figure 2 A picture of distilled water is given on the right.
[0040] S3, Drying
[0041] The obtained exfoliated dispersion solution was placed in an oven and baked at 350°C for 4 hours, the water was basically evaporated and the bentonite surface was dry. Figure 3 The figure shows the SEM image of the bentonite after pre-stripping, which shows that the bentonite has been partially sheared into a layered structure and stacked together.
[0042] AFM images of bentonite particles after pre-stripping are shown in Figure 2. Figure 4 As shown in Figure a, bentonite particles are about 20 μm in size. According to Figure b, the average thickness of the particles is about 500 nm. It can be seen that after shearing, the thickness of the sample is still relatively large.
[0043] S4, add H2O2 aqueous solution and freeze
[0044] Pour a 5% H2O2 aqueous solution into the solution until it covers the surface of the bentonite, stir for 60 minutes, and then place in a freezer and freeze at -10°C for 12 hours.
[0045] S5. Microwave heating
[0046] The frozen bentonite was thawed by microwave heating at a microwave power of 800 W, and H2O2 was thermally decomposed to peel off the interlayer structure of the bentonite, thereby obtaining a peeled bentonite dispersion slurry.
[0047] The freezing and heating operation was repeated once, and the technical parameters used in the second freezing and heating operation were the same as those in the first operation.
[0048] S6, drying to obtain finished product
[0049] The obtained bentonite dispersion slurry is placed in an oven and dried to obtain the finished product. The AFM image of the finished bentonite nanosheet is as follows: Figure 5 As shown, Figure 5 There are two two-dimensional bentonite nanosheets in the graph. The size of the small piece is about 2.1μm, and the size of the large piece is about 2.8μm. Figures b and c are the thickness of the small piece and the large piece respectively. The thickness of both pieces is about 5nm. The size has good uniformity.
[0050] The diameter, thickness, and diameter-to-thickness ratio of the finished bentonite nanosheets are shown in the following figure: Figure 6 As shown, the lateral diameter of the finished bentonite nanosheets is mostly distributed in the range of 0.5-2.0μm. The lateral diameter is relatively large. There are many two-dimensional sheets with a thickness of about 0-10nm and 5nm. The diameter-to-thickness ratio exceeds 100, and about 31% of the two-dimensional sheets have a diameter-to-thickness ratio in the range of 160-200.
[0051] Example 2
[0052] It was found that the pre-stripped bentonite was delaminated after being stationary. The original bentonite was subjected to X-ray diffraction. The XRD pattern of the original bentonite is as follows: Figure 7As shown. Through the XRD spectrum calculation, it can be known that the bentonite contains 79.4% montmorillonite, 6.8% albite, 5.7% quartz, 4.6% cristobalite and 3.5% orthorhombic calcium silicate. It can be seen that this material is the original bentonite in the mine. Among them, the 2θ angle corresponding to the montmorillonite (001) crystal plane is 5.89°. According to the Bragg law 2dsinθ=nλ, it can be seen that the interplanar spacing is 1.5nm. It can be seen that this bentonite is calcium-based bentonite. 5.89°, 19.7°, 29.5°, 34.7°, and 62.1° correspond to the (001)(100)(005)(110)(300) crystal planes of bentonite, respectively, and the pdf card is #01-0135.
[0053] Figure 8 This is the XRD diagram of bentonite after pre-stripping. It can be seen that the sample after shearing and extraction contains only bentonite and a small amount of cristobalite. According to XRD calculation, the content of montmorillonite is about 96.3%, and the content of cristobalite is about 3.7%. Therefore, after shearing, the purity of the sample is greatly improved. At the same time, the applicant found that compared with the sample before shearing, the diffraction peak of bentonite on the (001) crystal plane became more significant, while the diffraction peaks of other diffraction crystal planes were relatively weakened. This is because the sample is preferentially sheared along the layered direction, and the length of the crystal plane in the non-(001) direction is reduced, thereby weakening the Bragg diffraction intensity, resulting in a weakening of the diffraction peak intensity.
[0054] In fact, Chinese patent documents CN112174160A and CN117049557A disperse bentonite in lithium chloride or sodium chloride salt solution for ion exchange modification, which is also a way of removing impurities. Another innovation of the present application is that it utilizes high-speed shearing and layered separation to achieve the effect of interlayer peeling of bentonite and relatively simply remove impurities.
[0055] Comparative Example 1
[0056] Comparative Example 1 mainly examines the technical effect brought about by shearing and removing impurities.
[0057] Weigh 40g of the same batch of bentonite and directly pour a 5% H2O2 aqueous solution into it so that it covers the surface of the bentonite. The subsequent processing steps are the same as those in Example 1. After two cycles of freezing and heating, the finished product is subjected to electron microscopy scanning and X-ray diffraction. Fig. 9 , Fig.10 shown.
[0058] Fig. 9This is the diameter, thickness, and diameter-to-thickness ratio distribution diagram of the unpeeled finished bentonite nanosheets. The figure shows the lateral size distribution of the unsheared samples: 0-0.5μm accounts for 7%, 0.5-1.0μm accounts for 9%, 1.0-1.5μm accounts for 17%, 1.5-2.0μm accounts for 23%, 2.0μm to 2.5μm accounts for 24%, and 20% are above 2.5μm. Compared with the peeled samples, the lateral size has increased. This may be because the shearing operation reduces the size of the sample. Without the pre-peeling effect, the thickness of the sample has increased significantly. Most of the sample thickness is above 150nm, accounting for about 67%. Therefore, in Figure c, 53% of the nano two-dimensional sheets have a diameter-to-thickness ratio within 0-20, and about 20% have a diameter-to-thickness ratio of 20-40.
[0059] In the control sample without impurity removal treatment, the spectrum lines of impurities such as albite and quartz in the sample are weaker than those in the original sample, which means that the content is reduced. Fig.10 , XRD spectrum calculation, the sample contains 87.1% montmorillonite, 4.6% albite, 4.1% quartz, 1.8% cristobalite, and 2.4% orthorhombic calcite. Therefore, there are still many impurities in the unsheared sample.
[0060] Comparative Example 2
[0061] Comparative Example 2 mainly examines the technical effect brought about by the freezing diameter-to-thickness ratio.
[0062] Based on the steps of Example 1, only "freezing for 12 hours" is changed to "immersing at room temperature for 12 hours". After two freezing and heating, the diameter-to-thickness ratio of the solution in Example 1 is within the range of 160-200, accounting for more than 31%, and the diameter-to-thickness ratio is within the range of 100-160, accounting for more than 20%.
[0063] The diameter, thickness, and diameter-to-thickness ratio of the unfrozen finished bentonite nanosheets are shown in the following table. Fig.11 As shown, Fig.11 The diameter, thickness, and diameter-to-thickness ratio of the non-frozen nanosheets are distributed. About 58% of the nanosheets have a diameter less than 500 μm, and the thickness distribution range is relatively even in the range of 0-100 nm. In addition, 13% of the nanosheets have a diameter greater than 100 nm, and 57% of the diameter-to-thickness ratio is within 0-40. After two peelings, the effect is obviously not as good as that of Example 1 in which the freezing operation is added.
Claims
1. A method for preparing two-dimensional materials by exfoliating bentonite, characterized in that: Here are the steps: S1. Pre-stripping: Put bentonite into water, control the water temperature at 50-80°C, and perform high-speed shearing to pre-strip the bentonite sheet structure. The shearing speed is 3000-8000rpm and the duration is 10-20min. S2, impurity removal: the water body after shearing is still, and the impurities precipitated at the bottom are removed after stratification to obtain a stripping dispersion solution; S3, drying: drying the exfoliated dispersion solution until the surface of the bentonite is dry; S4. Add H2O2 aqueous solution and freeze: Pour H2O2 aqueous solution to cover the surface of bentonite, stir for not less than 30 minutes, and then place in a freezer at a freezing temperature of -18-0°C for not less than 60 minutes; S5, microwave heating: thawing the frozen bentonite by microwave heating, accompanied by thermal decomposition of H2O2, so that the interlayer structure of the bentonite is peeled off from each other, and a peeled bentonite dispersion slurry is obtained; S6. Drying to obtain the finished product: drying the obtained bentonite dispersion slurry to obtain the finished product.
2. The method for preparing two-dimensional materials by exfoliating bentonite according to claim 1, characterized in that: In the step S1, the material-liquid ratio of bentonite to water is 1:5-10.
3. The method for preparing two-dimensional materials by exfoliating bentonite according to claim 1, characterized in that: In step S3, the drying temperature is 250-400° C. and the drying time is 2-5 hours.
4. The method for preparing two-dimensional materials by exfoliating bentonite according to claim 1, characterized in that: In the step S4, the mass concentration of H2O2 in the H2O2 aqueous solution is 5-10%.
5. The method for preparing two-dimensional materials by exfoliating bentonite according to claim 1, characterized in that: In step S4, the freezing time is 1-12 hours.
6. The method for preparing two-dimensional materials by exfoliating bentonite according to claim 1, characterized in that: Before step S6, steps S4-S5 are repeated 1-2 times.
Citation Information
Patent Citations
Method for preparing two-dimensional material by boiling, vaporizing and stripping high-purity bentonite at normal temperature
CN112174160A
Two-dimensional material and preparation method and application thereof
CN113247868A
Method for preparing large high-quality two-dimensional nanosheet through low-frequency microwave thermal method
CN116675254A
Preparation method of two-dimensional montmorillonite nanosheet with high radius-thickness ratio
CN117049557A
Cited By
Two-dimensional flaky turbid liquid as well as preparation method and application thereof
CN121536922A